A Comparison of Performance among Exotic Meat Strains and Local Chicken Ecotypes under Sudan Conditions - Binda, B.D.; Yousif , I.A.; Elamin, K.M.; Eltayeb, H.E. (International Journal of Poultry Science, 2012)
The present study was conducted to compare the performance of exotic meat strains (Hybro and Hubbard) and native chicken ecotypes (Bare- neck, Large Beladi and Betwil) under hot climate of the Sudan. A total of 505 one day old chicks were reared together using a Completely Randomized Design with 9 replicates for each genotype. Traits studied up to 8 weeks of age were body weight, feed intake, live weight gain, feed conversion ratio and mortality. Results revealed that there were significant differences (p